Verbal encouragement does not improve maximal isometric hand grip strength in male judokas. A short report - Obminski, Z.; Mroczkowska, H. (Journal of Combat Sports and Martial Arts, 2015)
Introduction. The aim of this study was to investigate the effect of verbal encouragement (VE) on maximal isometric dominant hand grip strength (HGS) in male judo players. Material and methods. Using hand grip dynamometer, twelve male senior judokas of various body mass were assessed over 2 successive days. On each day, their maximal HGS was examined in a randomized order under 2 conditions, with VE from the coach and without VE. Both trials were separated by a 10-minute rest period, and each trial consisted of 3 attempts with a 2-minute intermission between trials. A two-way ANOVA (trial x day) was employed for detection of main effects. Results. Our calculations revealed that neither condition, nor the day of testing significantly affected HGS. The athletes reported a debilitating effect of VE on their attention focus and slightly lower scores were obtained during VE. Somewhat higher scores in HGS were noted on the second day, compared to the first, but the differences were not significant. Conclusion. In male judo player maximal HGS was not influenced by VE from the coach.